Spatiotemporal Properties of Vestibular Responses in Area MSTd - Fetsch, Christopher R. (American Physiological Society, 2010)
Recent studies have shown that many neurons in the primate dorsal medial superior temporal area (MSTd) show spatial tuning during inertial motion and that these responses are vestibular in origin. Given their well-studied role in processing visual self-motion cues (i.e., optic flow), these neurons may be involved in the integration of visual and vestibular signals to facilitate robust perception of self-motion. However, the temporal structure of vestibular responses in MSTd has not been characterized in detail. Specifically, it is not known whether MSTd neurons encode velocity, acceleration, or some combination of motion parameters not explicitly encoded by vestibular afferents. In this study, we have applied a frequency-domain analysis to single-unit responses during translation in three dimensions (3D). The analysis quantifies the stimulus-driven temporal modulation of each response as well as the degree to which this modulation reflects the velocity and/or acceleration profile of the stimulus. We show that MSTd neurons signal a combination of velocity and acceleration components with the velocity component being stronger for most neurons. These two components can exist both within and across motion directions, although their spatial tuning did not show a systematic relationship across the population. From these results, vestibular responses in MSTd appear to show characteristic features of spatiotemporal convergence, similar to previous findings in the brain stem and thalamus. The predominance of velocity encoding in this region may reflect the suitability of these signals to be integrated with visual signals regarding self-motion perception.